Defects-assisted ferromagnetism due to bound magnetic polarons in Ce into Fe, Co:ZnO nanoparticles and first-principle calculations. Issue 7 (2nd February 2016) - Verma, Kuldeep Chand; Kotnala, R. K.
Abstract : In the DMS systems of Zn0.94 Fe0.03 Ce0.03 O and Zn0.94 Co0.03 Ce0.03 O, the Ce ions attribute lattice defects as well as enhance antiferromagnetic interactions, which have potential in novel spintronic applications. Abstract : Zn0.94 TM0.03 Ce0.03 O [Zn0.94 Fe0.03 Ce0.03 O (ZFCeO) and Zn0.94 Co0.03 Ce0.03 O (ZCCeO)] nanoparticles were synthesized by a sol–gel process. Elemental analysis of these nanoparticles detects the weight percentage of Zn, Co, Fe, Ce and O in each sample. The Rietveld refinement of the X-ray diffraction pattern obtains the occupancy of dopant atoms, Wurtzite ZnO structure, crystallinity and lattice deformation with doping. The Ce doping into ZFO and ZCO form nanoparticles than nanorods was observed in pure ZnO, ZFO and ZCO samples that described due to chemical and ionic behavior of Ce, Fe, Co and Zn ions. The Raman active modes have peak broadening, intensity changes and peak shifts with metal doping that induces lattice defects. Photoluminescence spectra show blue-shifts at near-band edges and defects that influence broad visible emission with Ce doping. An enhancement in ferromagnetism in the magnetic hysteresis at 5 K is measured. The zero-field cooling and field cooling at H = 500 Oe and T = 300–5 K could confirm antiferromagnetic interactions mediated by defect carriers. The bound magnetic polaron at defect sites is responsible for the observed ferromagnetism. The ac magnetic susceptibility measurements determine the antiferromagnetic to ferromagnetic transition with some magnetic clustered growth in the samples and reveal a frequency independent peak that shows the Neel temperature. Weak room temperature ferromagnetism and optical quenching in ZFCeO are described by valance states of Fe and Ce ions, respectively. Using first-principle calculations, we studied the occupancy of Ce (replacing Zn atoms) in the Wurtzite structure.